The mediating role of perceived stress between smartphone dependency and psychological well-being among college students - Noradilah, Md Nordin; Martin, Peter (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2022)
Psychological well-being is one of the main elements in students’ life, especially for successful adaptation to the college environment. Determining what factors influence students’ psychological-well may provide valuable insights and ideas for the development of intervention programs. Therefore, this paper aims to examine the association between life events, smartphone dependency, perceived stress, and psychological well-being and whether perceived stress mediates the association between smartphone dependency and psychological well-being. Pearson correlations and multiple regression analyses with bootstrapped mediation were used to analyze the data in this study. The results show that life events were positively associated with perceived stress and that smartphone dependency was associated with higher perceived stress levels. Then, perceived stress was found negatively correlated with psychological well-being. However, smartphone dependency was not associated with psychological well-being. The bootstrapped analysis indicated that perceived stress fully mediated the association between smartphone dependency and psychological well-being. In summary, this study is significant for practitioners in well-being fields, such as counselors and educators, to promote students’ well-being in higher education.